LAWS with AI: How to aBANdon the Superiority - N. A. Samoylovskaya (Международная аналитика)
Taking the relative novelty of issues relating to the military use of AI and its influence on international relations into account, the author of this paper relies on the latest reports of international research centres, organizations and national programs on the issue. The paper considers the political consequences of the military use of AI, as well as the national and international approaches to mitigate its challenges. With great attention to the AI policies of two technological leaders in the field, the author concludes that a balanced U.S. policy will determine whether China and the United States will be able to create, despite the presence of competition, common rules for legalizing the use of AI systems in the military sphere and form common standards that include a high level of security in the use of these systems, including the proliferation of such weapons. The author points out that Europe’s concentration on the conflict with Russia and its exclusion from the environment created by the technical and ethical legal tools for using AI will increase unpredictability in relations. This is why it is in Europe’s interests to involve Russia in the development of a common platform and standards for AI. The development and establishment of common safety standards will help avoid problems with perception and introduce an element of predictability in international relations.